2002
DOI: 10.1002/1521-3757(20020301)114:5<829::aid-ange829>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Charakterisierung und Photochemie der Gallium- und Indiumsubhydride Ga2H2 und In2H2

Abstract: In dieser Arbeit beschreiben wir die Cokondensation von Ga-oder In-Dampf mit H 2 in Ar im ‹berschuss bei 10 ± 12 K und die nachfolgende Bestrahlung der erzeugten Matrix mit Licht unterschiedlicher Wellenl‰ngen. Wir zeigen, dass sich durch Umsetzung von Ga 2 oder In 2 mit H 2 direkt oder indirekt drei Ga 2 H 2 -Isomere und zwei In 2 H 2 -Isomere bilden: 1) die Bis(m-hydrido)-Spezies Ga(m-H) 2 Ga 1 a und In(m-H) 2 In 1 b, 2) die trans-gewinkelten Spezies HGaGaH 3 a und HInInH 3 b und 3) GaGaH 2 2 a mit zwei term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Electronically excited states can play a major role in reaction mechanisms involving these clusters. 3,4 The results of that work show that the reaction proceeds via an electronically excited state of Ga 2 . In general, the reactivity of clusters is higher than the one of a metal atom and of an ideal defect-free metal surface.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Electronically excited states can play a major role in reaction mechanisms involving these clusters. 3,4 The results of that work show that the reaction proceeds via an electronically excited state of Ga 2 . In general, the reactivity of clusters is higher than the one of a metal atom and of an ideal defect-free metal surface.…”
Section: Introductionmentioning
confidence: 82%
“…Ti 2 in its ground electronic state, 3 ⌬ g . For the harmonic vibrational frequency and the equilibrium distance of the 3 ⌬ g ground state, the literature reports experimental values of 407 cm Ϫ1 ͑Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first fully characterized main-group element compound which was shown to add dihydrogen under mild conditions belongs to this category [10]. Hence, the matrix-isolated metal-atom dimer Ga 2 ( 3 P u ground electronic state) [11] adds H 2 to give the cyclic Ga(I) compound Ga(m-H) 2 Ga (D 2h symmetry; see Scheme 26.1) [12,13]. Both, the Ga 2 reactant and the Ga(I) hydride product must be prevented from undergoing consecutive reactions by aid of the matrixisolation technique.…”
mentioning
confidence: 99%
“…However, no stable neutral GaGa bonded dimers of the general formula RGaGaR (R=organic or related group) have yet been described. Calculations on a variety of model species, including HGaGaH,10, 11, 1619 MeGaGaMe,9–11 and PhGaGaPh,11 as well as IR spectroscopy of HGaGaH in a frozen matrix19, 20 point to weak GaGa bonding. It is now shown that the compound Ar′GaGaAr′ ( 2 ; Ar′=2,6‐Dipp 2 C 6 H 3 , Dipp=2,6‐ i Pr 2 C 6 H 3 ), can be isolated and characterized with use of a terphenyl substituent (Ar′) that is closely related to the Ar* ligand employed in the synthesis of 1 .…”
mentioning
confidence: 99%